Odpowiedź :
x-długość prostokąta
y-szerokość prostokąta
xy-pole prostokąta
(x+4)(y+3)=xy+43
(x+7)y=xy+28
xy+3x+4y+12=xy+43
xy+7y=xy+28
3x+4y=31
7y=28
y=4
x=31-16
x=15
y=4
y-szerokość prostokąta
xy-pole prostokąta
(x+4)(y+3)=xy+43
(x+7)y=xy+28
xy+3x+4y+12=xy+43
xy+7y=xy+28
3x+4y=31
7y=28
y=4
x=31-16
x=15
y=4
y-szerokość prostokąta
x-długość prostokąta
xy-pole prostokąta
(x+4)(y+3)=xy+43
(x+7)y=xy+28
xy+3x+4y+12=xy+43
xy+7y=xy+28
3x+4y=31
7y=28
y=4
x=31-16
x=15
y=4
x-długość prostokąta
xy-pole prostokąta
(x+4)(y+3)=xy+43
(x+7)y=xy+28
xy+3x+4y+12=xy+43
xy+7y=xy+28
3x+4y=31
7y=28
y=4
x=31-16
x=15
y=4